Realizing the Potential of Neglected and Underutilized Bananas in Improving Diets for Nutrition and Health Outcomes in the Pacific Islands - Burkhart, Sarah; Underhill, Steven; Raneri, Jessica (Frontiers in Sustainable Food Systems, 2022)
Pacific Island countries are undergoing rapid food system transformation. This has led to a deterioration in diet quality with decreased consumption of traditional, fresh foods, and increasing consumption of imported, ultra-processed foods. Consequently, the triple burden of malnutrition is a now a major issue in the region. It is estimated that Vitamin A deficiency (VAD) is widespread, particularly in Kiribati, Vanuatu, and Solomon Islands. Rates of overweight, obesity, and diet-related non-communicable disease (DR-NCD) are high. Increasing consumption of local, traditional fruits and vegetables, particularly those that have high nutritional value like Pacific Island bananas, could play an important role in improving diets and health outcomes of Pacific Islander populations. Many of the banana cultivars found in the Pacific Islands region are high in carotenoids, an important precursor to Vitamin A. Fe'i bananas, such as Utin Iap, have been shown to contain much higher amounts of carotenoids than that of the commonly consumed Cavendish banana. As a traditional, starchy staple food, bananas are a good source of carbohydrate, including resistant starch, with small amounts of protein and little fat. These characteristics also lend themselves to being part of a healthy diet. The promotion of neglected and underutilized banana cultivars in the Pacific region provides a food-based and low-cost solution that simultaneously supports healthy diets and good nutrition, local farming systems and livelihood opportunities. However, to realize this potential, more work is required to understand the availability of nutrient rich banana in the region, current consumption patterns and drivers of consumption.